2022
DOI: 10.1172/jci147822
|View full text |Cite
|
Sign up to set email alerts
|

Iron deficiency linked to altered bile acid metabolism promotes Helicobacter pylori–induced inflammation–driven gastric carcinogenesis

Abstract: Gastric carcinogenesis is mediated by complex interactions among Helicobacter pylori , host, and environmental factors. Here, we demonstrate that H . pylori augmented gastric injury in INS-GAS mice under iron-deficient conditions. Mechanistically, these phenotypes were not driven by alterations in the gastric microbiota; however, discovery-based and targeted metabolomics revealed that bile acids were significantly altered in H … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
29
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 31 publications
(33 citation statements)
references
References 57 publications
0
29
0
Order By: Relevance
“…In their current, scientifically rigorous work in this issue of the JCI , Noto et al ( 19 ) greatly extended their previous work by using INS-GAS mice to confirm that iron deficiency exacerbates H . pylori –induced gastritis and dysplasia and elucidated the underlying mechanisms.…”
Section: H Pylori Plus Iron Deficiency Augment Gastric Cancermentioning
confidence: 89%
See 4 more Smart Citations
“…In their current, scientifically rigorous work in this issue of the JCI , Noto et al ( 19 ) greatly extended their previous work by using INS-GAS mice to confirm that iron deficiency exacerbates H . pylori –induced gastritis and dysplasia and elucidated the underlying mechanisms.…”
Section: H Pylori Plus Iron Deficiency Augment Gastric Cancermentioning
confidence: 89%
“…pylori –infected C57BL/6 and INS-GAS mice, Noto et al found that, compared with infected mice under iron-replete conditions, variants of muricholic acid, cholic acid, and deoxycholic acid (DCA) were markedly increased by H . pylori infection in iron-deficient animals ( 19 ). As proof of principle, treating INS-GAS mice with DCA augmented, while bile acid sequestration attenuated, H .…”
Section: Bile Acids Plus H Pylori ...mentioning
confidence: 99%
See 3 more Smart Citations